Understanding Emotion-Related Processes in Classroom Activities Through Functional Measurements - Prokofieva, Victoria; Kostromina, Svetlana; Polevaia, Sofia; Fenouillet, Fabien (Frontiers in Psychology, 2019)
Abstract To improve educational research focusing on such complex phenomenon as the interaction of emotion-related processes (affects) and students’ learning classroom activities, the collaboration between Educational studies and Neurosciences appears particularly relevant. Stress or ‘stress response’ being an emotion-related psychological process (Gross, 2014) having a neurobiological origin (Selye, 1956) is mostly studied in neurophysiological research using laboratory controlled objective measurements. One of such methods, HRV (heart rate variability) is considered as a reliable neurobiological correlate of stress response as the heart and the brain are directly and indirectly connected, which is advanced by the neurovisceral integration model (Thayer and Lane, 2000; Thayer and Lane, 2009). This article presents an empirical research which uses a neurophysiological HRV method of wireless measurement of stress response in students of 11-12 y.o. (N=12) during real-life classroom (oral and written) assessment activities and in 5 different lessons. The stress data was confronted to the analysis of the students’ behavior and the nature of classroom events through a video-based classroom observation. The results indicate that cardiovascular correlates of parasympathetic activity are instantaneous markers of stress response and correspond to real contextual elements of classroom assessment activities, among which the most stressful are: writing a short test, an oral reply to the question of the teacher, putting up hand to reply, etc. The stressful factors were highlighted, grouped and ranked. The longest stress duration was registered for oral reply at the blackboard. The total stress duration covered 38.8% of time spent in the classroom. This finding suggests that classroom assessment activities are stressful in young students as possibly representing social evaluation.